2021
DOI: 10.1371/journal.pone.0255612
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis of Salmonella enterica serovar Gallinarum biovars Pullorum and Gallinarum decodes strain specific genes

Abstract: Salmonella enterica serovar Gallinarum biovar Pullorum (bvP) and biovar Gallinarum (bvG) are the etiological agents of pullorum disease (PD) and fowl typhoid (FT) respectively, which cause huge economic losses to poultry industry especially in developing countries including India. Vaccination and biosecurity measures are currently being employed to control and reduce the S. Gallinarum infections. High endemicity, poor implementation of hygiene and lack of effective vaccines pose challenges in prevention and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 150 publications
(164 reference statements)
1
11
0
Order By: Relevance
“…enterica serovar Enteritidis str. P125109 (NC_011294.1) [ 52 ]. However, the GC content of the assembled genome (52.16%) was more similar to Salmonella enterica subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…enterica serovar Enteritidis str. P125109 (NC_011294.1) [ 52 ]. However, the GC content of the assembled genome (52.16%) was more similar to Salmonella enterica subsp.…”
Section: Discussionmentioning
confidence: 99%
“…enterica serovar Enteritidis str. P125109 (NC_011294.1) (52.17%) [ 52 ]. HiSeq assemblies have been traditionally considered the “gold standard” because MinION sequencing could introduce high numbers of errors and consequently may interfere with high-quality genome annotations due to reduced accuracy in gene prediction, producing a large number of misannotated genes [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…S. Gallinarum strains also present several different genomic profiles, including lineages with several prophages, plasmids, and gene clusters coding for different AMR mechanisms [75,88]. It has also been reported that S. Gallinarum has accumulated many pseudogenes and virulence genes associated with specificity to chicken hosts [89].…”
Section: Salmonella Gallinarummentioning
confidence: 99%
“…However, egg contamination can lose its association with causing foodborne illness, as exemplified by the closely related serotypes S. gallinarum and S. pullorum . These two serotypes are host-restricted to the bird and are not a cause of human foodborne illness [ 64 ]. They are threats to food security because of high transmittance and mortality in chicks and mature birds [ 65 ].…”
Section: The Infection Pathway Of Salmonella Enterica ...mentioning
confidence: 99%